Cardiac self-limiting rhabdomyomas in a neonatal patient with tuberous sclerosis complex: a case report with negative genetic testing - Zhou, Huatao; Zheng, Zilong; Tu, Zhi; Li, Yichen; Yang, Jinfu; Fan, Chengming (Frontiers in Pediatrics, 2023)
Background: Tuberous Sclerosis Complex (TSC) is a hereditary condition that leads to the development of non-malignant neoplasms in various organs, including cardiac rhabdomyomas, which can cause significant complications.Case presentation: This report describes the case of a 15-day-old male neonate who was hospitalized due to intracardiac masses and brain lesions, despite the absence of TSC gene mutations. The patient's mother exhibited facial angiofibromas, a common feature of TSC. Over a 2-year follow-up period, spontaneous regression of the cardiac tumor was observed.Conclusions: This case illustrates that not all TSC cases exhibit detectable TSC gene mutations. Current treatment strategies, such as mTOR inhibitors, offer potential effectiveness in managing associated cardiac rhabdomyomas. Further research should focus on evaluating the therapeutic potential of these inhibitors.